2020
DOI: 10.2196/19028
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a National Web-Based Heart Age Calculator for Cardiovascular Disease Prevention: User Characteristics, Heart Age Results, and Behavior Change Survey

Abstract: Background Heart age calculators are used worldwide to engage the public in cardiovascular disease (CVD) prevention. Experimental studies with small samples have found mixed effects of these tools, and previous reports of population samples that used web-based heart age tools have not evaluated psychological and behavioral outcomes. Objective This study aims to report on national users of the Australian heart age calculator and the follow-up of a sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Heart age calculators can work well as a marketing tool to get attention and direct consumers to appropriate clinical assessments or lifestyle change, 93 but caution is needed to ensure they are not used to nudge low-risk people toward medications and tests that they are unlikely to benefit from in the short term. 94 A registered trial (ACTRN12620000806965) will soon test the effect of adding heart age to a cardiovascular disease prevention decision aid for the first time, to investigate how it affects decision making.…”
Section: Time-based Risk Formatsmentioning
confidence: 99%
“…Heart age calculators can work well as a marketing tool to get attention and direct consumers to appropriate clinical assessments or lifestyle change, 93 but caution is needed to ensure they are not used to nudge low-risk people toward medications and tests that they are unlikely to benefit from in the short term. 94 A registered trial (ACTRN12620000806965) will soon test the effect of adding heart age to a cardiovascular disease prevention decision aid for the first time, to investigate how it affects decision making.…”
Section: Time-based Risk Formatsmentioning
confidence: 99%
“…Firstly, amongst those who were shown their heart age, gist knowledge of percentage risk was initially improved, but after 4 weeks gist and verbatim knowledge were higher for heart age than for percentage risk. Previous studies have shown that people receiving an older heart age may react defensively and focus on other information, such as a low short-term risk level, which in turn may reduce credibility of the risk result 24,58 . Analyses of people who received an older heart age result suggests it may be useful as a marketing tool to get attention and initiate behaviour change, but knowledge of heart age did not translate to knowledge of risk.…”
Section: Discussionmentioning
confidence: 99%
“…In considering how to power such trials, researchers will need to consider how the specific heart age tool they are using is calibrated for the intended population (e.g. ∼50% older in our sample using NZ method versus ∼80% in Australian/UK HF tool 23,24 ). The primary outcome also needs to carefully considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations